2020
DOI: 10.1177/0271678x20946198
|View full text |Cite
|
Sign up to set email alerts
|

Binding of the synaptic vesicle radiotracer [11C]UCB-J is unchanged during functional brain activation using a visual stimulation task

Abstract: The positron emission tomography radioligand [11C]UCB-J binds to synaptic vesicle glycoprotein 2 A (SV2A), a regulator of vesicle release. Increased neuronal firing could potentially affect tracer concentrations if binding site availability is altered during vesicle exocytosis. This study assessed whether physiological brain activation induces changes in [11C]UCB-J tissue influx ( K1), volume of distribution ( VT), or binding potential ( BPND). Healthy volunteers ( n = 7) underwent 60-min [11C]UCB-J PET scans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…Our recent study in healthy control participants showed that [ 11 C]UCB-J K 1 is highly sensitive to increased blood flow induced by visual stimulation, with no effects on synaptic density measures ( V T ). 33 Our previous study in AD demonstrated broad regional differences in K 1 in temporoparietal cortices relative to CN, 11 similar to the pattern of known cortical hypometabolism in AD. Similar concepts have been investigated previously in the early dynamic flow images of PET with amyloid tracers.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Our recent study in healthy control participants showed that [ 11 C]UCB-J K 1 is highly sensitive to increased blood flow induced by visual stimulation, with no effects on synaptic density measures ( V T ). 33 Our previous study in AD demonstrated broad regional differences in K 1 in temporoparietal cortices relative to CN, 11 similar to the pattern of known cortical hypometabolism in AD. Similar concepts have been investigated previously in the early dynamic flow images of PET with amyloid tracers.…”
Section: Discussionmentioning
confidence: 53%
“…2931 We have previously reported a low test-retest variability (3-9%) of [ 11 C]UCB-J V T across all brain regions in the same human participants, 32 and have also observed that [ 11 C]UCB-J PET V T for synaptic density is stable in the presence of blood flow changes as with those accompanying visual stimulation. 33 This excellent reproducibility and non-stimulation-dependent quantification of [ 11 C]UCB-J PET could potentially be advantageous for use in longitudinal studies and clinical trials. Of note, most of the previous analyses for [ 11 C]UCB-J PET studies including our first study in early AD 11 were conducted using white matter (WM) in the centrum semiovale (CS) as the reference region.…”
Section: Introductionmentioning
confidence: 97%
“…This is unlike 11 C-UCB-J PET, which quantifies the vesicular SV2A protein, and reflects synaptic density which is considered a structural measure and unlikely to fluctuate with increase or decreases in neural activity. Furthermore, a recent study found that during visual-activation tasks, 11 C-UCB-J V T remain unchanged, while blood flow increased as reflected in increased K 1 values ( Smart et al, 2020b ). Thus, differences in ICA-derived networks between these modalities are not unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging synaptic density has investigated with a number of PET ligands targeting the SV2A presynaptic vesicle glycoprotein with [ 11 C]-UCB-J having the best pharmacological characteristics [7] and being the most established clinically to date [1,8,9,[15][16][17][18][19][20][21][22][23][24][25][26][27]. This study reports radiation dosimetry for [ 11 C]-UCB-J using two versions of the OLINDA dosimetry software.…”
Section: Discussionmentioning
confidence: 99%